Effects of ICT-Based Multicomponent Program on Body Composition and Cognitive Function in Older Adults: A Randomized Controlled Clinical Study - Kim DR (Dove Medical Press, 2021)
Du-Ri Kim1,2 *, Seunghwan Song1,3 *, Gwon-Min Kim,1 Jae Hyeok Chang,1,4 Young Jin Tak,5 Up Huh,1,3 Jeong Su Cho,3 Yung Liao,6 Kap-Soo Han,7 Myoung-Hwan Ko,7,8 Jong-Hwan Park1 1Health Convergence Medicine Laboratory, Biomedical Research Institute, Pusan National University Hospital, Busan, Korea; 2Department of Occupational Therapy, Graduate School of Inje University, Gimhae, Korea; 3Department of Thoracic and Cardiovascular Surgery, School of Medicine, Pusan National University, Department of Thoracic and Cardiovascular Surgery, Pusan National University Hospital, Busan, Korea; 4Department of Rehabilitation Medicine, School of Medicine, Pusan National University, Department of Rehabilitation Medicine, Pusan National University Hospital, Busan, Korea; 5Department of Family Medicine, Pusan National University Hospital, Busan, Korea; 6Department of Health Promotion and Health Education, National Taiwan Normal University, Taipei, Taiwan; 7Research Institute of Clinical Medicine of Jeonbuk National University-Biomedical Research Institute of Jeonbuk National University Hospital, Jeonju, Korea; 8Department of Physical Medicine and Rehabilitation, Jeonbuk National University Medical School, Jeonju, Korea*These authors contributed equally to this workCorrespondence: Myoung-Hwan KoDepartment of Physical Medicine and Rehabilitation, Jeonbuk National University Medical School, 20 Geonji-ro, Deokjin-gu, Jeonju, 54907, KoreaTel +82-63-250-1785Email mhko@jbnu.ac.krJong-Hwan ParkHealth Convergence Medicine Laboratory, Biomedical Research Institute, Pusan National University Hospital, 179, Gudeok-Ro, Seo-Gu, Busan, 49241, KoreaTel +82-51-240-7071Email parkj@pusan.ac.krPurpose: Information and communication technology (ICT)-based training devices for older adults’ care related to dementia are being developed to enhance older adults’ cognitive functions. Older adults who require bicycle training devices can improve muscle strength and balance of lower limbs by continuously contracting and relaxing lower-limb muscles and improving cognitive function to prevent dementia. This study was conducted to investigate the effects of an ICT-based multicomponent program on body composition and cognitive function in older adults.Patients and Methods: In a randomized controlled intervention test on 20 people over the age of 60 (exercise group: n = 10; control: n = 10), the multicomponent program was applied to the exercise group twice per week, once per day for 12 weeks, at 30 min per session, whereas the control group was advised to maintain their usual daily activities.Results: Comparing body composition changes and cognitive function changes before and after intervention exhibited statistically significant differences in skeletal muscle mass (P=0.01) and modified Alzheimer’s disease assessment scale–cognitive score (P=0.01) between the two groups.Conclusion: It can be difficult to be engaged in a simple repetitive exercise program. Therefore, to meet older adults’ interests and expectations, a customized ICT-based multicomponent program, which can improve body composition and cognitive function in older adults and is believed to help prevent dementia, is recommended.Trial Registration: UMIN000042129 (https://www.umin.ac.jp/english/).Keywords: ICT-based multicomponent program, body composition, cognitive function, dementia, older adults